Avaliação química e farmacológica de extratos secos das folhas de espécies de pedra-ume-caá - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The plant species that popularly known as pedra-ume-caá are used in popular medicine in Brazil for the treatment of diabetes, and the plant raw material is sold throughout the country. Therefore, the leaves of different pedra-ume-caá species were collected in three locations: Embrapa Amazônia Ocidental - Amazonas state [Myrcia multiflora (MmEAO) and Eugenia punicifolia (EpEAO)]; in the Adolpho Ducke Forest Reserve - Amazonas state [M. sylvatica (MsylRAD) and E. punicifolia (EpRAD)], and in an environmental protection area - Pará state [M. multiflora (MmAPA), M. sylvatica (MsylAPA), M. guianensis (MguAPA), M. amazonica (MamAPA), E. punicifolia (EpAPA) and E. biflora (EbAPA)]. The dry extracts of these species and 17 commercial samples acquired in Manaus, Belém and Goiânia were prepared by infusion. All extracts were analysed using HPLC-HRMS and NMR, then subjected to chemometric analysis (PCA and HCA) and NMRq (native samples). The antidiabetic effect of dry extracts was evaluated according to their inhibition of -glucosidase, -amylase and lipase, as well as to their content of total phenols, in vitro cell viability, free radical scavenging and antiglycation activities. Oral maltose tolerance (EbAPA and EpEAO) and chronic multiple dose tests (EbAPA and MmAPA) in streptozotocin-induced diabetic mice (STZ) were performed over 28 days. Subsequently, biochemical parameters, hemolysis, and levels of the thiobarbituric acid reactive species in the liver were investigated and histopathological analyses of the kidneys and liver were performed. In total, 22 phenolic compounds, 1 organic acid and 3 carbohydrates were characterized. By using qNMR, this study demonstrated that quercitrin, hyperoside and corilagin have high concentrations in the dry extract of the sample MmAPA, as well as catechin in the dry extract of the sample EbAPA. In the analysis of the loadings graphs of the three main components (68.01%), we were able to conclude that quinic acid, gallic acid, catechin, myricitrin and quercitrin are the main chemical markers of these species. Furthermore, these markers were identified in 15 commercial samples. MmAPA, MmEAO, EpEAO, EpAPA, EpRAD and EbAPA showed inhibition activity of the enzyme -glucosidase. However, no inhibition was observed against the other enzymes. Chronic administration of EbAPA (50 mg/kg of body weight) and MmAPA (25 mg/kg and 50 mg/kg bw) reduced glucose levels in diabetic animals similar to acarbose. These results are associated with catechin, myricitrin, quercitrin, B-type procyanidin and corilagin, which are present in these extracts. However, EbAPA (100 and 200 mg/kg bw) caused premature death of mice up to 22 days of treatment. Our data indicate that one of the mechanisms of toxicity of EbAPA may be related to the aggravation of oxidative stress in the liver. This histopathological study indicated that EbAPA failed to minimize the progression of the toxicity of diabetes caused by STZ. Therefore, this study enabled the identification of plant raw materials sold as pedra-ume-caá, since the results showed the main chemical markers of these species. In addition, we demonstrated the hypoglycemic potential of E. biflora and M. multiflora leaves. However, the use of the infusion of EbAPA for a prolonged period can be harmful to its users due to its considerable toxicity, which needs to be better investigated.
Keywords: Hipoglicemiantes; Compostos fenólicos; CIENCIAS EXATAS E DA TERRA: QUIMICA; Myrcia; Eugenia; Compostos fenólicos; Inibição enzimática; Hipoglicêmico; Myrcia; Eugenia; Phenolic compound; Enzyme inhibition; Hypoglycemic